Characteristic of praseodymium oxide doped manganese/ruthenium catalyst in methanation: effect calcination temperature / Salmiah Jamal Mat Rosid ... [et al.] - Jamal Mat Rosid, Salmiah; Toemen, Susilawati; Wan Abu Bakar, Wan Azelee; Mat Rosid, Sarina; Wan Abdullah, Wan Nazwanie; Aziz, Siti Maisarah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Lanthanide element in the methanation reaction gives an excellent catalytic performance at low reaction temperature. Praseodymium is one of lanthanide element and was chosen due to its properties which are thermally stable and provide excess of oxygen in the oxide lattice. Therefore, a catalyst of Ru/Mn/Pr (5:30:65)/Al2O3 (RMP, 5:30:65/Al2O3) was prepared via wetness impregnation method and the effect of calcination temperature on the catalyst performance was investigated using FTIR analysis. The RMP/Al2O3 catalyst calcined at 800 o C was chosen as an excel catalyst with CO2 conversion of 96.9% and CH4 formation of 45.1% at 350 o C reaction temperature. From the EDX mapping, it can be observed that the distribution of all element is homogeneous at 800 o C and 900 o C except Ru, O and Al at 1000 o C calcination temperature. The image from FESEM also shows the presence of some crystal shape on the catalyst surface. From the FTIR analysis, the peak stretching and bending mode of O-H bond decreased when the calcination temperature increased.